The Impact of Microagression in Counseling on The Mental Health of Students - Layyinatus Syifa (Universitas Sebelas Maret, 2019)
This article examines the microagressions carried out by counselors in the counseling process that have an impact on the mental health of students. With a literature study the author tries to identify the forms of microagression, the impact of microagression in the counseling process, and strategies that can be done to overcome microagression. The background of this writing is based on the many stereotypes that appear in society towards certain groups viewed from the origin, race, religion, gender, sexual orientation. The writing of this article is expected to help guide efforts to recognize, minimize and respond to microagress in the counseling process.